Predators And Parasitoids Species Of Spodoptera frugiperda J. E. Smith On Corn Plant In North Minahasa Regency - Karundeng, Aknes; Mamahit, Julliet Merry Eva; Kandowangko, Daisy Sandra (Jurnal Agroekoteknologi Terapan, 2024)
This study aims to determine the types of predators and parasitoids of S. frugiperda in North Minahasa Regency. This study used descriptive explorative method with 2 stages, namely the sampling stage in the field, 27 samples of S. frugiperda egg groups were taken from corn plantations that were 1-2 weeks old and then maintained in the laboratory until they hatched and samples of predators and parasitoids of S. frugiperda larvae were taken from corn plantations that were 4 weeks old and had not been sprayed with pesticides. The next stage is observation in the laboratory, samples of predators and parasitoids of S. frugiperda are observed by looking at their morphological characteristics then the results of this study are presented in the form of descriptive tables and figures. The results of this study found 5 types of predators on S. frugiperda, namely Tetraqnatha sp. (Aranae: Tetragnathidae), Paederus sp. (Coleoptera: Staphilinidae), Cheilomenes sp. (Coleoptera: Coccinellidae), Neurothemis sp. (Odonata: Libellulidae), and Family Forficulidae Order Dermaptera, for parasitoid species found 2 types of egg parasitoids and 1 type of larval parasitoid, the type of egg parasitoid S. frugiperda is Trichogramma sp. (Hymenoptera: Trichogrammatidae), Telenomus sp. (Hymenoptera: Scelionidae) and the type of larval parasitoid Apanteles sp. (Hymenoptera: Braconidae). Keywords: Predators, Parasitoids, Spodoptera frugiperda, Corn Abstrak Penelitian ini bertujuan untuk mengetahui jenis-jenis predator dan parasitoid S. frugiperda di Kabupetan Minahasa Utara. Penelitian ini menggunakan metode deskriptif exploratif dengan 2 tahap yaitu tahap pengambilan sampel di lapangan, 27 sampel kelompok telur S. frugiperda  diambil dari areal pertanaman jagung yang berumur 1-2 minggu kemudian dipelihara di laboratorium sampai menetas dan sampel predator dan parasitoid larva S. frugiperda diambil dari areal pertanaman jagung yang berumur 4 minggu dan belum dilakukan penyemprotan pestisida. Tahap selanjutnya yaitu pengamatan di  laboratorium, sampel predator dan parasitoid S. frugiperda di amati dengan melihat karakteristik morfologinya kemudian hasil penelitian ini disajikan dalam bentuk deskriptif tabel dan gambar. Hasil penelitian ini ditemukan 5 jenis predator pada S. frugiperda yaitu Tetraqnatha sp. (Aranae : Tetragnathidae), Paederus sp. (Coleoptera : Staphilinidae), Cheilomenes sp. (Coleoptera : Coccinellidae), Neurothemis sp. (Odonata : Libellulidae), dan Famili Forficulidae Ordo Dermaptera, untuk jenis parasitoid ditemukan 2 jenis parasitoid telur dan 1 jenis parasitoid larva,  jenis parasitoid telur S. frugiperda yaitu Trichogramma sp. (Hymenoptera : Trichogrammatidae), Telenomus sp. (Hymenoptera : Scelionidae) dan jenis parasitoid larva Apanteles sp. (Hymenoptera : Braconidae). Kata kunci : Predator, Parasitoid, Spodoptera frugiperda, Jagung